Mixed conductive additive for solid-state battery as well as preparation method and application of mixed conductive additive
By using a mixed conductive additive prepared by mixing grinding and sintering of the first conductive agent, the second conductive agent and the solid electrolyte in the solid battery, the weak interface between the solid electrolyte and the electrode material in the solid battery is solved. Problem, the carrier transmission efficiency and the cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411452455.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
AI Technical Summary
The effective contact between the solid electrolyte and the electrode material in a solid-state battery is weak, resulting in low carrier transmission efficiency, low capacity retention rate and poor stability after multiple cycles.
Using a method of preparing a mixed conductive additive, including a first conductive agent pretreatment, mixed grinding and sintering step, the first conductive agent, the second conductive agent and the solid electrolyte are prepared with one step after the mixing of the first conductive agent, the second conductive agent and the solid electrolyte. and compatible hybrid conductive additives.
It improves the carrier transmission efficiency of solid-state batteries, extends the cycle life of the battery, and maintains a high capacity after multiple cycles, improving the stability of the battery.
Smart Images

Figure CN119481055A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive additives, and in particular to a mixed conductive additive for solid-state batteries and a preparation method and application thereof. Background Art
[0002] As a new type of electrochemical energy storage device, solid-state batteries have the advantages of high safety, high energy density and long life; however, the low carrier transfer efficiency of solid-state batteries limits their performance improvement.
[0003] In solid-state batteries, the interface between the solid electrolyte and the electrode material is a solid-solid interface, and the effective contact between the two is weak, which makes the carrier transmission power in the solid material low, and then leads to low carrier transmission efficiency, which in turn leads to low capacity retention rate after multiple cycles of the battery.
[0004] Therefore, how to establish ion channels in the solid-solid interface of solid-state batteries, improve the efficiency of carrier transfer, and prevent the low capacity retention and poor stability of the battery after multiple cycles is an urgent problem to be solved. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a method for preparing a mixed conductive additive for solid-state batteries, aiming to solve the problems in the prior art of weak effective contact between the solid electrolyte and the electrode material of the solid-state battery, low carrier transfer efficiency, resulting in low capacity retention and poor stability of the battery after multiple cycles.
[0006] In order to solve the above technical problems, the purpose of the present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention discloses a method for preparing a mixed conductive additive for a solid-state battery, comprising the following steps:
[0008] S1: pre-treatment of the first conductive agent: submerging the first conductive agent mixed oil bath with concentrated nitric acid solution, washing and drying to obtain the treated first conductive agent;
[0009] S2 mixed grinding: mixing and grinding the treated first conductive agent, the second conductive agent, the solid electrolyte and the solvent, and drying to obtain a precursor;
[0010] S3 sintering: sintering the precursor to obtain a mixed conductive additive for solid-state batteries;
[0011] Wherein, the solid electrolyte is selected from at least one of Li2S, LiCl, P2S5, LiBr, LiI, SiS2, GeS2 or SnS2;
[0012] The first conductive agent is selected from at least one of conductive carbon black, Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, graphene or porous carbon;
[0013] The second conductive agent is selected from at least one of conductive carbon black, Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, graphene or porous carbon;
[0014] The mass ratio of the treated first conductive agent, the second conductive agent and the solid electrolyte is (1-6): (1-6):3.
[0015] Optionally, the sintering parameters are: heating rate 1-5°C / min, holding temperature 300-550°C, and holding time 8-16h.
[0016] Optionally, the parameters of the oil bath are: temperature 50-250° C., time 1-12 h.
[0017] Optionally, the second conductive agent is porous carbon, the pore size of the second conductive agent is 1-3000nm, and the specific surface area is 60-600m 2 / g.
[0018] Optionally, the second conductive agent is dried, and the parameters of the drying process are: temperature 50-150° C., time 1-24 h.
[0019] Optionally, the ratio of the total volume of the treated first conductive agent, the second conductive agent and the solid electrolyte to the volume of the solvent is 1:(1-5).
[0020] Optionally, the solvent is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isoamyl ether, butyl isobutyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate.
[0021] Optionally, the mass fraction of the concentrated nitric acid solution is greater than or equal to 40%.
[0022] On the other hand, the present invention discloses a mixed conductive additive for solid-state batteries, which is prepared by the above-mentioned method for preparing the mixed conductive additive for solid-state batteries.
[0023] The present invention also discloses the use of the above-mentioned mixed conductive additive for solid-state batteries in the preparation of solid-state batteries.
[0024] Beneficial effects:
[0025] The preparation method of the mixed conductive additive for solid-state batteries of the present invention obtains the mixed conductive additive by mixing and grinding a first conductive agent, a second conductive agent and a solid electrolyte and then sintering the mixed conductive additive in one step. The preparation method is simple, the sintering temperature is low, the preparation cycle is short, the cost is low, and it is suitable for large-scale mass production. The prepared mixed conductive additive has good stability and compatibility. When used in the preparation of solid-state batteries, a tighter 3D contact can be constructed to ensure that the electrode material of the solid-state battery is in physical contact with the electron / ion conductive agent after multiple cycles, so that the utilization rate of the active material is improved, thereby improving the carrier transmission efficiency of the solid-state battery and the capacity retention rate after multiple cycles, and can also extend the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.
[0027] Figure 1 This is a schematic diagram of a solid-state battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0030] A method for preparing a mixed conductive additive for a solid-state battery comprises the following steps:
[0031] S1 Pretreatment of the first conductive agent: After the concentrated nitric acid solution is submerged in the first conductive agent mixed oil bath, the first conductive agent is cleaned and dried to obtain the treated first conductive agent.
[0032] The first conductive agent is selected from at least one of conductive carbon black (Super P), Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, graphene or porous carbon. The first conductive agent is preferably acetylene black.
[0033] The mass fraction of the concentrated nitric acid solution is preferably greater than or equal to 40%. The first conductive agent is etched with concentrated nitric acid so that the first conductive agent has a loose and porous structure, which is convenient for mixing with the second conductive agent and the solid electrolyte in the subsequent process, and more solid electrolyte is loaded on the surface, thereby better constructing a mixed conductive additive. The mass fraction of the concentrated nitric acid solution is more preferably 65%.
[0034] The parameters of the oil bath are preferably: temperature 50-250°C, time 1-12h. More preferably, the parameters of the oil bath are: temperature 50-150°C, time 8-12h.
[0035] Deionized water may be used during the cleaning process to remove the acid remaining on the first conductive agent after the oil bath.
[0036] After cleaning, it can be dried by blast drying and then vacuum drying to improve drying efficiency; specifically, a large amount of moisture on the surface of the first conductive agent is removed by blast drying at 50-80°C, and then transferred to a vacuum drying oven and dried at 50-150°C for 1-24 hours to obtain the treated first desiccant. Preferably, the blast drying temperature is 60°C, and the vacuum drying is 80-120°C for 10-14 hours.
[0037] S2 mixed grinding: the treated first conductive agent, the second conductive agent, the solid electrolyte and the solvent are mixed and ground, and then dried to obtain a precursor.
[0038] Wherein, the solid electrolyte is selected from at least one of Li2S, LiCl, P2S5, LiBr, LiI, SiS2, GeS2 or SnS2; preferably, the solid electrolyte is selected from at least one of Li2S, LiCl, P2S5, LiBr or LiI; more preferably, the solid electrolyte is selected from at least one of Li2S, LiCl or P2S5.
[0039] The second conductive agent is selected from at least one of conductive carbon black, Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, graphene or porous carbon. The second conductive agent is dried, and the parameters of the drying treatment are: temperature 50-150°C, time 1-24h. Preferably, the parameters of the drying treatment are: temperature 80-120°C, time 4-14h. The purpose of drying is to remove water from the second conductive agent to prevent the second conductive agent from carrying moisture and contacting with subsequent solid electrolytes, so that the solid electrolyte reacts with water, affecting the structure and performance of the prepared mixed conductive additive.
[0040] The second conductive agent may preferably be porous carbon; the second conductive agent is preferably a porous carbon having a pore size of 1-3000 nm and a specific surface area of 60-600 m 2 / g porous carbon; more preferably, the pore size is 1-3μm, the specific surface area is 60-100m 2 / g of porous carbon.
[0041] The mass ratio of the treated first conductive agent, the second conductive agent and the solid electrolyte is preferably (1-6): (1-6):3.
[0042] The solvent is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isoamyl ether, butyl isobutyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate.
[0043] The ratio of the total volume of the treated first conductive agent, the second conductive agent and the solid electrolyte to the volume of the solvent is preferably 1:(1-5). That is, the volume ratio of the mixture of the first conductive agent, the second conductive agent and the solid electrolyte to the solvent is preferably 1:(1-5), and more preferably 1:(1-3).
[0044] The grinding parameters are preferably: rotation speed 300-500rpm, time 1-24h; the purpose of grinding is to make the treated first conductive agent, second conductive agent and solid electrolyte mix evenly, wherein the solvent can not only act as a lubricant and dispersant to make the mixing smoother and more efficient, but also promote the friction and agglomeration between the particles of the mixture, change the shape of the particles of the mixture, and prevent the outside air from contacting and reacting with the mixed particles.
[0045] The parameters for drying the uniformly ground mixture are: temperature 40-200° C., time 1-24 h; preferably, temperature 80-120° C., time 10-14 h.
[0046] This step is performed in an inert atmosphere. Specifically, the inert atmosphere may be an argon atmosphere, a helium atmosphere, or the like.
[0047] S3 sintering: sintering the precursor to obtain a mixed conductive additive for solid-state batteries;
[0048] The sintering parameters are: heating rate 1-5°C / min, holding temperature 300-550°C, holding time 8-16h; sintering is one-step sintering.
[0049] A mixed conductive additive for solid-state batteries is prepared by the above-mentioned preparation method of the mixed conductive additive for solid-state batteries and can be used in the preparation of solid-state batteries.
[0050] Experimental Example 1: A mixed conductive additive for solid-state batteries is prepared by the following method.
[0051] S1 Pretreatment of the first conductive agent: Mix the first conductive agent with concentrated nitric acid, cover the first conductive agent with the concentrated nitric acid, reflux in an oil bath at 100°C for 10 hours, wash with deionized water to remove residual acid on the surface after cooling, dry with air at 60°C to remove a large amount of water, transfer to a vacuum drying oven and dry at 100°C for 12 hours to obtain the treated first conductive agent.
[0052] The first conductive agent is acetylene black, and the mass fraction of concentrated nitric acid is 65%.
[0053] S2 mixed grinding: the treated first conductive agent, the second conductive agent, the solid electrolyte mixture and the solvent are mixed in a zirconia tank, and then run at a speed of 500 rpm for 8 hours to obtain a wet mixture, and then the wet mixture is placed in a vacuum drying oven at 100°C for 12 hours to obtain a dry mixed conductive additive precursor.
[0054] The second conductive agent has been pre-treated by drying at 100°C for 12 hours. The second conductive agent has a pore size of 3 μm and a surface area of 80 m 2 / g porous carbon; the solid electrolyte contains Li2S, LiCl and P2S5, with a mass ratio of 5:1:2; the mass ratio of the treated first conductive agent, the second conductive agent and the solid electrolyte is 3:3:4; the volume ratio of the mixture to the solvent is 1:2, and the solvent is isobutyl isobutyrate. All the above operations are carried out in an inert atmosphere.
[0055] S3 sintering: The precursor is placed in a muffle furnace for high-temperature sintering, and the temperature is raised to 500°C at a heating rate of 1°C / min and sintered for 12 hours to obtain a mixed conductive additive for solid-state batteries.
[0056] Experimental Example 2: A mixed conductive additive for solid-state batteries is prepared by the following method.
[0057] S1 Pretreatment of the first conductive agent: Mix the first conductive agent with concentrated nitric acid, cover the first conductive agent with the concentrated nitric acid, reflux in an oil bath at 50°C for 12 hours, wash with deionized water to remove residual acid on the surface after cooling, dry with air at 80°C to remove a large amount of moisture, transfer to a vacuum drying oven and dry at 80°C for 14 hours to obtain the treated first conductive agent.
[0058] The first conductive agent comprises conductive carbon black, vapor-grown carbon fibers and carbon nanotubes, and the mass ratio of the three is 1:1:1; and the mass concentration of concentrated nitric acid is 45%.
[0059] S2 mixed grinding: the treated first conductive agent, the second conductive agent, the solid electrolyte mixture and the solvent are mixed in a zirconia tank, and then run at a rotation speed of 300 rpm for 10 hours to obtain a wet mixture, and then the wet mixture is placed in a vacuum drying oven at 100°C for 12 hours to obtain a dry mixed conductive additive precursor.
[0060] The second conductive agent has been pre-treated by drying at 50°C for 16 hours. The second conductive agent has a pore size of 1 μm and a surface area of 100 m 2 / g of porous carbon and graphene, carbon nanotubes, and vapor-grown carbon fibers, the mass ratio of the four being 1:1:1:1;
[0061] The solid electrolyte contains LiBr, LiI, SiS2 and GeS2 in a mass ratio of 2:3:1:4; the mass ratio of the treated first conductive agent, the second conductive agent and the solid electrolyte is 1:6:3; the volume ratio of the mixture to the solvent is 1:1, and the solvent is ethyl acetate. All the above operations are carried out in an inert atmosphere.
[0062] S3 sintering: The precursor is placed in a muffle furnace for high-temperature sintering, and the temperature is raised to 300°C at a heating rate of 3°C / min and sintered for 16 hours to obtain a mixed conductive additive for solid-state batteries.
[0063] Experimental Example 3: A mixed conductive additive for solid-state batteries is prepared by the following method.
[0064] S1 Pretreatment of the first conductive agent: Mix the first conductive agent with concentrated nitric acid, cover the first conductive agent with the concentrated nitric acid, reflux in an oil bath at 150°C for 8 hours, wash with deionized water to remove residual acid on the surface after cooling, dry with air at 40°C to remove a large amount of moisture, transfer to a vacuum drying oven and dry at 120°C for 10 hours to obtain the treated first conductive agent.
[0065] The first conductive agent comprises Ketjen black, conductive graphite, graphene and porous carbon, the mass ratio of the four is 2:1:3:2, and the mass concentration of concentrated nitric acid is 80%.
[0066] S2 mixed grinding: the treated first conductive agent, the second conductive agent, the solid electrolyte mixture and the solvent are mixed in a zirconia tank, and then run at a speed of 400 rpm for 9 hours to obtain a wet mixture, and then the wet mixture is placed in a vacuum drying oven at 100°C for 12 hours to obtain a dry mixed conductive additive precursor.
[0067] The second conductive agent has been pre-treated by drying at 150°C for 4 hours. The second conductive agent includes a pore size of 100 nm and a surface area of 60 m 2 / g porous carbon and conductive carbon black, Ketjen black, acetylene black, and conductive graphite, the ratio of the five is 1:2:3:1:3; the solid electrolyte contains SnS2 and P2S5, the mass ratio is 1:2; the mass ratio of the treated first conductive agent, the second conductive agent, and the solid electrolyte is 6:1:3; the volume ratio of the mixture to the solvent is 1:5, and the solvent is isopropyl ether. All the above operations are carried out in an inert atmosphere.
[0068] S3 sintering: The precursor is placed in a muffle furnace for high-temperature sintering, and the temperature is raised to 550°C at a heating rate of 5°C / min and sintered for 8 hours to obtain a mixed conductive additive for solid-state batteries.
[0069] At the same time, comparative test examples 1-9 are set, and the differences between comparative test examples 1-9 and test example 1 are as follows.
[0070] Table 1 The difference between comparative examples 1-9 and test example 1
[0071]
[0072] Example 1, a solid-state battery, the preparation method is as follows.
[0073] N1 Preparation of composite positive electrode: In a glove box filled with argon, a lithium nickel cobalt manganese oxide positive electrode (LiNi 0.8 Co 0.1 Mn 0.1 O2), sulfide solid electrolyte, conductive agent and mixed conductive additive are manually ground in a mortar according to a certain proportion for 10 minutes until they are evenly mixed to obtain a composite positive electrode material.
[0074] Wherein, the sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11- x M 2-x P 1+x S 12 (M=Ge, Sn, Si, x=0-2) or more; preferably, Li6PS5Cl;
[0075] The conductive agent is selected from one or more of conductive carbon black (SuperP), Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; preferably, it is vapor-grown carbon fiber;
[0076] In terms of mass percentage, in the composite positive electrode, the nickel cobalt manganese oxide lithium positive electrode is configured to be 60-90wt%, the solid electrolyte is configured to be 5-30wt%, the conductive agent is configured to be 0.1-5wt%, and the mixed conductive additive is configured to be 0.1-5wt%;
[0077] Specifically, in the composite positive electrode, the positive electrode active material, lithium nickel cobalt manganese oxide, is configured to be 70wt%, the solid electrolyte Li6PS5Cl is configured to be 27wt%, and the conductive agent, vapor-grown carbon fiber, is configured to be 1.5wt%; the mixed conductive additive is experimental example 1, configured to be 1.5wt%.
[0078] Preparation of Li-In negative electrode with N2: In a glove box filled with argon, cut indium foil and lithium foil according to the mass ratio of In:Li=98:2, then place them on a tablet press for pressing, tighten the pressure rod, and then obtain Li-In alloy sheet.
[0079] N3 assembles solid-state batteries: first weigh 0.1g of sulfide solid electrolyte powder and place it in a mold sleeve, cold press it at 360MPa for 5 minutes, then lay the composite positive electrode and Li-In negative electrode sheets on both sides of the sulfide solid electrolyte layer, and then cold press it at 50MPa pressure. Finally, tighten the screws to seal the mold to obtain a solid-state battery.
[0080] The sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11-x M 2-x P 1+ x S 12 (M=Ge, Sn, Si, x=0-2) or more; preferably, Li6PS5Cl. Specifically, the sulfide solid electrolyte is Li6PS5Cl.
[0081] Example 2, a solid-state battery, the preparation method is as follows.
[0082] N1 Preparation of composite positive electrode: In a glove box filled with argon, a lithium nickel cobalt manganese oxide positive electrode (LiNi 0.8 Co 0.1 Mn 0.1 O2), sulfide solid electrolyte and conductive agent are manually ground in a mortar according to a certain proportion for 10 minutes until they are evenly mixed to obtain a composite positive electrode material.
[0083] The sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11-x M 2-x P 1+ x S 12 (M=Ge, Sn, Si, x=0-2) or more; preferably, Li6PS5Cl.
[0084] The conductive agent is selected from one or more of conductive carbon black (SuperP), Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; preferably, it is vapor-grown carbon fiber.
[0085] In terms of mass percentage, in the composite positive electrode, the nickel cobalt manganese oxide lithium positive electrode is configured to be 60-90wt%, the solid electrolyte is configured to be 5-3wt%, and the conductive agent is configured to be 0.1-5wt%.
[0086] Specifically, in the composite positive electrode, the positive electrode active material, lithium nickel cobalt manganese oxide, is configured to be 70wt%, the solid electrolyte Li6PS5Cl is configured to be 27wt%, and the conductive agent, vapor-grown carbon fiber, is configured to be 3wt%.
[0087] Preparation of composite negative electrode by N2: In a glove box filled with argon, silicon powder, sulfide solid electrolyte, conductive agent and mixed conductive additive were manually ground in a mortar at a mass ratio of 60:30:5:5 for 20 min until they were evenly mixed to obtain a composite negative electrode material.
[0088] The sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11-x M 2-x P 1+ x S 12 (M=Ge, Sn, Si, x=0-2) or more; preferably, Li6PS5Cl.
[0089] The conductive agent is selected from one or more of conductive carbon black (SuperP), Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, and graphene; preferably, it is vapor-grown carbon fiber.
[0090] In terms of mass percentage, in the composite negative electrode, the silicon powder is configured to be 40-80wt%, the solid electrolyte is configured to be 20-50wt%, the conductive agent is configured to be 1-10wt%, and the mixed conductive additive is configured to be 1-10wt%.
[0091] Specifically, in the composite negative electrode, the negative electrode active material silicon is configured to be 60wt%, the solid electrolyte Li6PS5Cl is configured to be 30wt%, and the conductive agent vapor-grown carbon fiber is configured to be 5wt%; the mixed conductive additive is embodiment 1, configured to be 5wt%.
[0092] N3 assembles solid-state batteries: first weigh 0.1g of sulfide solid electrolyte powder and place it in a mold sleeve, cold press it at 360MPa for 5 minutes, then lay the composite positive electrode and composite positive electrode powder on both sides of the sulfide solid electrolyte layer, and then cold press it at 200MPa for 5 minutes, and finally tighten the screws to seal the mold to obtain a solid-state battery.
[0093] The sulfide solid electrolyte is selected from Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11-x M 2-x P 1+ x S 12 (M=Ge, Sn, Si, x=0-2) or more; preferably, Li6PS5Cl. Specifically, the sulfide solid electrolyte is Li6PS5Cl.
[0094] At the same time, according to Example 1-2, the following examples and comparative examples are set; the differences between Example 3-4 and Comparative Example 1-11 and Example 1-2 are shown in the following table.
[0095] Table 2 Differences between Examples 3-4 and Comparative Examples 1-11 and Examples 1-2
[0096]
[0097]
[0098] The solid-state batteries prepared in Examples 1-4 and Comparative Examples 1-11 were subjected to the following tests, and the test results data table obtained is shown in the following table.
[0099] First cycle discharge capacity test: tested using NEWARE battery test system, which is the ratio of the first cycle discharge capacity to the mass of the positive electrode active material;
[0100] Coulomb efficiency test: tested using NEWARE battery test system, which is the percentage of the first cycle discharge capacity to the charge capacity;
[0101] 1C cycle 100 cycles capacity retention test: The test was conducted using the NEWARE battery testing system, which is the capacity retention rate after 100 cycles at a cycle rate of 1C;
[0102] Cycle life test: The capacity retention rate is theoretically calculated based on 100 cycles at 1C. The number of cycles when the capacity retention rate is 80% is the theoretical cycle life of the battery.
[0103] Among them, the coulombic efficiency can reflect the reversibility of lithium ion extraction / insertion, but cannot directly reflect the cycle stability; a high coulombic efficiency indicates that the electrode has high electrochemical activity, the side reactions may be more intense, and the cycle decay is faster.
[0104] Table 3 Performance test results of Examples 1-4 and Comparative Examples 1-11
[0105]
[0106] According to Table 3, the solid-state batteries prepared in Examples 1-4 have relatively good stability; among them, the solid-state battery prepared in Example 1 is as follows Figure 1 shown.
[0107] Among them, by comparing Example 1 with Example 3, and Example 2 with Example 4, it can be seen that the mixed conductive additive prepared in Test Example 1 is better than the mixed conductive additives prepared in Test Examples 2 and 3.
[0108] By comparing Example 1 with Comparative Example 1, and Example 2 with Comparative Example 2, it can be seen that the first-cycle discharge specific capacity and coulomb efficiency of the all-solid-state battery (Example 1-2) assembled with the positive / negative electrode containing a mixed conductive additive are slightly lower than those of the all-solid-state battery (Comparative Example 1-2) assembled with the positive / negative electrode without conductive additives. This is mainly because the electron channels / ion channels in the mixed conductive additives are more concentrated, so the spatial dispersion is worse, which will lead to a certain degree of polarization. However, after 100 cycles at a rate of 1C, the capacity retention rate of the all-solid-state battery (Example 1-2) assembled with the positive / negative electrode containing a mixed conductive additive is significantly higher than that of the all-solid-state battery (Comparative Example 1-2) assembled with the positive / negative electrode without conductive additives. This is because at a high rate, the requirements for the electron / ion transport rate are higher, and the concentrated mixed conductive channels can transmit electrons / ions in time, reduce the tortuosity of the electrode, and improve battery performance.
[0109] By comparing Example 1 with Comparative Examples 3-11, it can be seen that the mixed conductive additive prepared in Experimental Example 1 has good stability and compatibility. When used in the preparation of solid-state batteries, it can construct a tighter 3D contact to ensure that the electrode material of the solid-state battery is in physical contact with the electron / ion conductive agent after multiple cycles, thereby improving the utilization rate of the active material, thereby improving the carrier transfer efficiency of the solid-state battery, the capacity retention rate after multiple cycles, and extending the cycle life of the battery.
[0110] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing a mixed conductive additive for solid-state batteries, characterized in that: The following steps are involved: S1: pre-treatment of the first conductive agent: submerging the first conductive agent mixed oil bath with concentrated nitric acid solution, washing and drying to obtain the treated first conductive agent; S2 mixed grinding: mixing and grinding the treated first conductive agent, the second conductive agent, the solid electrolyte and the solvent, and drying to obtain a precursor; S3 sintering: sintering the precursor to obtain a mixed conductive additive for solid-state batteries; Wherein, the solid electrolyte is selected from at least one of Li2S, LiCl, P2S5, LiBr, LiI, SiS2, GeS2 or SnS2; The first conductive agent is selected from at least one of conductive carbon black, Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, graphene or porous carbon; The second conductive agent is selected from at least one of conductive carbon black, Ketjen black, acetylene black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, graphene or porous carbon; The mass ratio of the treated first conductive agent, the second conductive agent and the solid electrolyte is (1-6): (1-6):
3.
2. The method for preparing a mixed conductive additive for solid-state batteries according to claim 1, characterized in that: The sintering parameters are: heating rate 1-5°C / min, holding temperature 300-550°C, and holding time 8-16h.
3. The method for preparing a mixed conductive additive for solid-state batteries according to claim 1, characterized in that: The parameters of the oil bath are: temperature 50-250° C., time 1-12 h.
4. The method for preparing a mixed conductive additive for solid-state batteries according to claim 1, characterized in that: The second conductive agent is porous carbon, the pore size of the second conductive agent is 1-3000nm, and the specific surface area is 60-600m 2 / g.
5. The method for preparing a mixed conductive additive for solid-state batteries according to claim 1, characterized in that: The second conductive agent is dried, and the parameters of the drying process are: temperature 50-150° C., time 1-24 hours.
6. The method for preparing a mixed conductive additive for solid-state batteries according to claim 1, characterized in that: The ratio of the total volume of the treated first conductive agent, the second conductive agent and the solid electrolyte to the volume of the solvent is 1:(1-5).
7. The method for preparing a mixed conductive additive for solid-state batteries according to claim 1, characterized in that: The solvent is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isoamyl ether, butyl isobutyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate.
8. The method for preparing a mixed conductive additive for solid-state batteries according to claim 1, characterized in that: The mass fraction of the concentrated nitric acid solution is greater than or equal to 40%.
9. A mixed conductive additive for solid-state batteries, characterized in that: The mixed conductive additive for solid-state batteries is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the mixed conductive additive for solid-state batteries according to claim 9 in the preparation of solid-state batteries.
Citation Information
Patent Citations
Lithium ion battery capable of being charged and discharged at large rate under ultralow temperature and preparation method thereof
CN109713302A
Carbon nanotube oil system conductive paste containing solid-state electrolyte and preparation method of carbon nanotube oil system conductive paste
CN110415888A
Electrode for all-solid battery and manufacturing method thereof, and all-solid battery and manufacturing method thereof
JP2021039887A
Production process for alkali metal-sulfur batteries having high volumetric and gravimetric energy densities
US20170207488A1